2005
DOI: 10.1007/s00134-005-2711-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Y-piece of the ventilation circuit on ventilation requirements in extremely low birth weight infants

Abstract: CO2 elimination time with and without closed suction device was nearly identical for the Y-piece without flow sensor and for the dead-space free-flow sensor. With both systems, ventilation requirements were significantly lower than for the integrated flow sensor and for the small dead-space flow sensor (integrated flow sensor vs dead-space free-flow sensor 23.6 and 24.5%, respectively, small dead-space flow sensor vs dead-space free flow sensor 11.7 and 10.9%, respectively); thus, we think that introduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…This phenomenon was previously observed in vivo 4 and implied in bench tests. 21,24 This study actually demonstrated that the CO 2 elimination was complete in the bench model.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…This phenomenon was previously observed in vivo 4 and implied in bench tests. 21,24 This study actually demonstrated that the CO 2 elimination was complete in the bench model.…”
Section: Discussionmentioning
confidence: 57%
“…20,21 These models eliminate the uncontrollable variables that are often present in living beings. The model used by Wald et al 21 is based on measurement of the CO 2 removal rate from a test lung connected to a ventilator with the equipment under the test. Using this model was especially attractive because the model permits the direct measurement of the patientrelevant parameters of the respiratory equipment.…”
Section: Introductionmentioning
confidence: 99%
“…We devised a modification of a technique used previously to evaluate the effect of various configurations of flow sensors on the effectiveness of CO 2 removal 13. The simple premise of our approach is that if the V T is insufficient to clear the DS, then no CO 2 is washed out from the test lung and none is detected by the ETCO 2 sensor.…”
Section: Methodsmentioning
confidence: 99%
“…This has a relevant effect on ventilation requirements, especially in ELBW neonates, which can be particularly unfavorable during the weaning procedure [23,24]. Furthermore, it might contribute to the development of chronic lung disease by increasing volutrauma [24]. Additionally, the catheter might considerably compromise ventilation if accidentally not drawn back entirely.…”
Section: Discussionmentioning
confidence: 99%
“…The built-in Y-connector, imposing an extra volume of 2 ml compared to 0.4 ml for the regular tube adapter, represents a disadvantage. This has a relevant effect on ventilation requirements, especially in ELBW neonates, which can be particularly unfavorable during the weaning procedure [23,24]. Furthermore, it might contribute to the development of chronic lung disease by increasing volutrauma [24].…”
Section: Discussionmentioning
confidence: 99%